STUDI LITERATUR : PERAN PENDIDIKAN KEWARGANEGARAAN DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI PERSEKOLAHAN - Yunan, Ali; Tetep (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Civic Education (CE) is a strategic instrument within the national education system that plays a crucial role in shaping the character and personality of students in the school environment. This literature study aims to analyze the urgency and contribution of Civic Education as a moral foundation for the younger generation, particularly in facing the challenges of moral degradation and disruption in the digital era. The results of the study indicate that Civic Education functions not only as a transfer of knowledge regarding statehood but also as a means of internalizing the noble values of Pancasila, discipline, tolerance, and social responsibility. Effective implementation of Civic Education in schools is capable of transforming student behavior to be more democratic and possess high integrity. Amidst the dynamics of the times, Civic Education acts as an ethical filter that equips Generation Z with digital citizenship literacy to mitigate the negative impacts of information technology. The success of this character building is highly influenced by innovative learning methods, teacher role modeling, and the creation of a school ecosystem that supports the consistent practice of national values. Overall, strengthening civic education in schools is a fundamental investment in producing citizens who are intellectually intelligent and possess noble character.